EVALUASI KINERJA STRUKTUR RANGKA BETON BERTULANG BANGUNAN EKSISTING DI SAMARINDA - Maverick, Josh; Joelin, Gerard Christian; Kusbiantoro, Krismanto; Lesmana, Cindrawaty (JMTS: Jurnal Mitra Teknik Sipil, 2025)
Building repurposing is a common practice within the construction industry. Ensuring the safety of a structure is a crucial thing during the process. In the context of supporting the development of the Chinatown area in Samarinda, a safety evaluation of existing buildings in Samarinda City was conducted. The main goal of this evaluation was to evaluate the structural safety when building repurposing. The assessment employed multiple methods, including the Rapid Visual Screening (RVS) method, the story drift analysis, the P-Delta effect evaluation, and the FEMA 440 pushover analysis. Those analyses were selected to provide a thorough examination of the buildings' structural performance under various conditions. The results revealed a difference among the results. Specifically, the buildings passed the safety criteria set by the Rapid Visual Screening, the inter-story drift analysis, and the P-Delta effect evaluation. However, the buildings did not meet the safety requirements when evaluated using the FEMA 440 pushover analysis. The results indicate that in the pushover analysis, additional structures such as cantilever structures can be the first elements to fail during an earthquake. Abstrak Alih fungsi menjadi hal yang umum dilakukan pada bangunan. Ketika melakukan alih fungsi, Pemeriksaan terhadap keamanan bangunan perlu diperiksa. Dalam mendukung proses pembangunan kawasan pecinan di Samarinda, pemeriksaan pada bangunan eksisting di Kota Samarinda dilakukan dengan tujuan memeriksa keamanan bangunan saat bangunan akan dialih fungsikan. Pemeriksaan dilaksanakan dengan metode Rapid Visual Screening, analisa simpangan antar tingkat, evaluasi pengaruh P-Delta, dan analisa pushover FEMA 440. Cara ini dipilih untuk memberikan pemeriksaan menyeluruh terhadap kinerja struktural bangunan dalam berbagai kondisi. Hasil menunjukan bahwa setiap analisa memliki hasil yang berbeda antara satu sama lain, dimana bangunan dinyatakan lulus dalam Rapid Visual Screening, analisa pemeriksaan simpangan antar tingkat dan evaluasi pengaruh P-Delta, namun belum memenuhi dalam analisa pushover FEMA 440. Hasil menunjukan bahwa dalam analisa pushover, struktur tambahan seperti struktur kantilever dapat menjadi struktur yang menyebabkan kegagalan struktur pertama kali ketika terjadinya gempa.